THE FEATURES OF THE JAPANESE AND POLISH LANGUAGE OF LAW - HORIE, Yuki; TRZASKAWKA, Paula (Comparative Legilinguistics, 2016)
The subject of the paper was chosen because the features of language of law have not been described in every language pair yet. The aim of the paper is to discuss the features of the Japanese and Polish language of law. The presented features were taken from Polish and Japanese copyright acts, national terminology and language used in courts. The method focuses on empirical studies. The authors of the paper focus on the following features of language of law: polysemy and homonymy, synonyms, metaphors, false friends (faux amis) or specialized terminology, as well as differences between colloquial language and the varieties of the language of the law. The paper has an outlook nature. Only some features of language of law were chosen. In the nearest future the description of these features should be broadened, as well as the examples.